An empirical study of professional translators’ attitudes, use and awareness of Web 2.0 technologies, and implications for the adoption of emerging technologies and trends - Gough, Joanna (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This questionnaire-based study was conducted as a part of an MA Dissertation in the summer of 2010 (Gough, 2010a). It examines the trends within the translation industry which have developed in response to the evolution of the Web from Web 1.0 (the information web) to Web 2.0 (the social web) and places professional translators against the backdrop of these trends. The developments based on the principles of sharing, openness and collaboration associated with Web 2.0 can be seen as affecting the tools used by translators and the processes in which they engage. This study examines professional translators’ awareness and perception of the new open, collaborative tools and processes and the degree of tools usage and process participation. The key findings of this study highlight translators’ vague awareness and insufficient understanding of these trends, marginal use of the open tools and little engagement in the collaborative processes. The underlying factor determining translators’ awareness, perception and the use of these tools and processes is their attitude towards adopting new technologies, with an indication that professionals with innovative attitudes are more inclined to embrace the new trends and developments.